Accident Analysis on the Arteri Yos Sudarso street - Sarebni, Ahmad Viky Furqon; Setiadji, Bagus Hario; Narendra, Alfa (Eduvest - Journal of Universal Studies, 2025)
The Yos Sudarso arterial road, a critical ring road connecting industrial zones and ports in Central Java, experiences high accident rates (averaging 6 accidents/month from 2019 to 2022). Despite its economic significance, inadequate traffic signage and complex topography contribute to recurring accidents, necessitating a targeted safety analysis. This study investigates (1) the correlation between road complementary devices (e.g., traffic signs) and accident rates, and (2) the relationship between traffic volume and accident frequency, with a focus on high-risk vehicle groups. Field surveys and spatial analysis were conducted to evaluate road conditions, signage compliance, and accident hotspots. Data from 262 accidents were analyzed alongside traffic volume measurements and road equipment assessments. Key results include: (1) A strong correlation between insufficient traffic signs and accident occurrence, and (2) An inverse relationship between traffic volume and accidents, with Group 1 vehicles (e.g., cargo trucks) identified as most vulnerable. While compliant with regulations, road geometries revealed blind spots due to median vegetation. The study advocates for enhanced signage and ITS integration (e.g., adaptive signals) to mitigate accidents. It also calls for dedicated lanes for high-risk vehicles and further research into behavioral factors underlying the traffic volume paradox. These findings contribute to evidence-based policies for arterial road safety in urban-industrial corridors.